Food processing to reduce mycotoxins in Africa - Fandohan, P.; Hell, K.; Marasas, W.F.O. (2008)
Mycotoxins have both economic and health impacts because they contaminate human food and animal feeds. A central question is whether there are food processing strategies that reduce mycotoxin levels in food products. In this chapter we critically review food processing methods tested in Africa for their efficacy in reducing mycotoxin contamination in maize and peanut. These methods include cleaning, separation of screenings, washing, steeping, aqueous extraction, dehulling, milling, fermentation, cooking and roasting. Some methods reduced mycotoxin levels significantly while others were less effective. Encouraging the widespread use of the toxin-reducing processing techniques would lower consumption of contaminated food products in Africa, and improve food quality and human health.